Do asset prices reflect fundamentals? Freshly squeezed evidence from the OJ market - Boudoukh, Jacob; Richardson, Matthew; Shen, YuQing (Jeff); Whitelaw, Robert F. (Journal of Financial Economics, 2007)
The behavioral finance literature cites the frozen concentrated orange juice (FCOJ) futures market as a prominent example of the failure of prices to reflect fundamentals. In contrast, we show that when theory clearly identifies the fundamental, e.g., at temperatures close to or below freezing, a close link exists between FCOJ prices and that fundamental. Using a simple, theoretically motivated, nonlinear, state dependent model, we can explain approximately 50% of the return variation on days with freezing temperatures. Moreover, while these observations represent less than 4.5% of the winter sample, they account for two-thirds of the entire winter return variability.